2020
DOI: 10.46266/njes.1001
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect of nano and bulk TiO2 on growth, chlorophyll a content and oxidative stress of marine diatom Chaetoceros muelleri

Abstract: Nanoparticles are widely used in many applications. The recent increase in nanomaterials usage has led to raising concerns about its health risks and environmental impact. In this study, we examined the toxicity effects of nanoparticles TiO 2 and bulk Ti on marine diatom chatetoceros muelleri. We treated microalgae with equal amounts of nano and bulk TiO 2 in different concentrations include 0, 10, 50, 100, 200 and 300 ppm, then was investigated their growth in 96 h. Observations demonstrated growth inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Nanoparticles (NPs), along with genetic engineering and artificial intelligence, are commonly referred to as the cutting-edge technologies of the 21st century. NPs have the properties of stability, hydrophilicity, photocatalysis, nonirritant, good weatherability and shading in mechanics, heat, magnetism, optics, electricity and chemistry ( Huang et al., 2019 ; Baharlooeian and Badhul, 2020 ). They can be applied in targeted drug delivery, diagnosis, tissue engineering and environmental remediation ( Gandhimathi et al., 2019 ; Bidast et al., 2020 ; Santelli et al., 2020 ; Bajpai et al., 2022 ; Shukla et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles (NPs), along with genetic engineering and artificial intelligence, are commonly referred to as the cutting-edge technologies of the 21st century. NPs have the properties of stability, hydrophilicity, photocatalysis, nonirritant, good weatherability and shading in mechanics, heat, magnetism, optics, electricity and chemistry ( Huang et al., 2019 ; Baharlooeian and Badhul, 2020 ). They can be applied in targeted drug delivery, diagnosis, tissue engineering and environmental remediation ( Gandhimathi et al., 2019 ; Bidast et al., 2020 ; Santelli et al., 2020 ; Bajpai et al., 2022 ; Shukla et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, with the wide application of TiO 2 NPs, their safety profile has attracted greater attention recently. It has been reported that TiO 2 NPs may be more toxic to organisms than TiO 2 coarse particles ( Wei et al., 2018 ; Baharlooeian and Badhul, 2020 ). Its safety has been widely studied in agriculture, medicine, environmental and other fields ( Dreno et al., 2019 ; Fattahi et al., 2021 ; Fiordaliso et al., 2022 ), and is a global current research hotspot ( Wu et al., 2014 ; Shi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%